The Individual Inclination to an Occupation and its Neuronal Correlate - Gurres, Stefan; Dillmann, Klaus-Ulrich; Reith, Wolfgang; Krick, Christoph M. (Frontiers in Education, 2021)
Many young people decide their professional direction during adolescence. This often co-incides with vulnerable phases of puberty-related maturation that is usually accompanied by dif-ficulties in assessing one’s personal inclinations and competences. Several psychological tests have been established among teachers and career advisers serving as a tool for professional coaching the teenagers’ competences and preferences. Many tools are based on the “Theory of Vocational Personalities in Work Environment” developed by John L. Holland since the 1950s, comprising the ‘RIASEC’ model. Today, this theory provides the basis for tests which are used and refined all over the world. Professor Stangl's online assessable “Situational Interest Test” (SIT) is based on Hol-land's theory. By means of 30 short assessments the SIT questionnaire assesses the partici-pant’s personality traits: Realistic (“Doers”), Investigative (“Thinkers”), Artistic (“Creators”), Social (“Helpers”), Enterprising (“Persuaders”), and Conventional (“Organizers”). Modern Magnetic Resonance Imaging (MRI) is able to discriminate between the brain’s compartments as Gray and White Matter using Voxel-Based Morphometry (VBM). This tool al-lows to reshape and to normalize human brains’ structure to statistically examining individual brains. Up to now findings from 20 years of functional MRI gave detailed insights in correlations between brain structures and mental functions. Hence, knowledge on structural base of cogni-tive or behavioral patterns is available as a brain’s map for assigning anatomical regions to their functions. The present study demonstrates that there are statistically relevant correlations between all dimensions of Holland’s RIASEC theory by assessing individual professional inclinations and the neuronal structures of the brain. Results show correspondence between the personality traits assigned by the RIASEC test and the functions of significant structural alterations in distinct brain areas well-known from literature.